1985
DOI: 10.1093/schbul/11.3.364
|View full text |Cite
|
Sign up to set email alerts
|

"Negative Symptoms": Conceptual and Methodological Problems

Abstract: Research into the so-called negative symptoms of schizophrenia is plagued by often ignored problems in item identification, scale selection, quantification, clinical assessment process, and symptom (and, probably, causal) nonspecificity. Neither a negative symptom syndrome per se nor the recent rating scales designed to measure it have been validated, although some data useful in this regard have been presented for the scales. Since no criterion against which to validate these scales exists, construct validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
2
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(62 citation statements)
references
References 67 publications
(70 reference statements)
1
57
2
2
Order By: Relevance
“…In addition, the stimuli may have differed along dimensions other than cognitive demand, such as a social-nonsocial dimension. Despite these caveats, our results suggest that if a causal relation between cognitive deficits and affective flattening does exist, it is probably more complex than we had originally anticipated.Although it has been suggested that affective flattening may be caused by neuroleptic agents (e.g., Sommers, 1985), a simple relation between medication and emotional expression was not found in this study. The blunted and nonblunted schizophrenics were receiving equivalent types and amounts of medication, which indicates that the administration of neuroleptic agents is not sufficient to cause affective flatness.…”
contrasting
confidence: 88%
“…In addition, the stimuli may have differed along dimensions other than cognitive demand, such as a social-nonsocial dimension. Despite these caveats, our results suggest that if a causal relation between cognitive deficits and affective flattening does exist, it is probably more complex than we had originally anticipated.Although it has been suggested that affective flattening may be caused by neuroleptic agents (e.g., Sommers, 1985), a simple relation between medication and emotional expression was not found in this study. The blunted and nonblunted schizophrenics were receiving equivalent types and amounts of medication, which indicates that the administration of neuroleptic agents is not sufficient to cause affective flatness.…”
contrasting
confidence: 88%
“…Typically it involves a loss of contact with reality through hallucinations (a sensory perception experienced in the absence of an external stimulus, Silbersweig et al, 1995) and/or delusions (strongly held beliefs, maintained despite a lack of evidence, Bentall, Corcoran, Howard, Blackwood, & Kinderman, 2001) and is often concomitant with negative symptoms (e.g., withdrawal or lack of thoughts, feelings, and behaviors that are usually present, Sommers, 1985). These experiences are among the clinical hallmarks of many psychiatric diagnoses including schizophrenia, schizoaffective disorder, and bipolar disorder.…”
Section: P R E P U B L I C a T I O N C O P Ymentioning
confidence: 99%
“…103 Its construct validity and neurobiological correlates remain ambiguous. [104][105][106] As no theorybased rule exists for classifying the symptoms of schizophrenia as negative or positive, the distinction is supported by their differential loadings on separate factors. The argument is somewhat circular, since cross-sectional symptomatology is typically assessed by rating scales designed a priori to reflect such distinction.…”
Section: Molecular Psychiatrymentioning
confidence: 99%